High Dose Methotrexate and Leucovorin Rescue Therapy in Childhood Malignancies: Experience in Resource-Limited Country - Ferdousi, Shormin Ara; Akhter, Afroza; Nahar, Kamrun; Islam, Afiqul (Bangladesh Journal of Child Health, 2017)
Background: Administration of high dose methotrexate (HDMTX) needs meticulous monitoring. Limitations in the availability of trained staff and adequate infrastructure often are great problems in the developing country like Bangladesh. Objective: The aim of this study was to evaluate the HDMTX toxicities by monitoring biochemical and serological markers where facility for serum MTX level in a tertiary care centre (Combined Military Hospital, Dhaka) of Bangladesh is available. Methods: An explorative study was done among twelve cases with a confirmed diagnosis of Pre-B & T cell ALL, Burkitts lymphoma, T cell lymphoma and osteosarcoma. All of them received four cycles of HDMTX as part of their treatment. Demographic profile, details of HDMTX infusion and Leucovorin rescue and toxicities were collected and analyzed. Results: We evaluated and compared toxicity of repeated courses of high dose methotrexate (HDMTX) in five groups of pediatric patients. Neutropenia was observed in 83.3% case and vomiting in 70% during chemotherapy. Diarrhoea 12.5%, oral mucositis in 56.20% patients were noted. Low hemoglobin level, was observed in 14.58%, thrombocytopenia in 20.80% patients. Vomiting and diarrhea was most frequent in cycle 2>1>3>4, whereas mucositis, fever was most frequent in Cycle 1>2>3>4 and raised serum transaminase in cycle 3>2>1>4. Two patients had <100 creatinine clearance. There was significant relationship between neutropenia with toxicities like vomiting and mucositis (p<0.05). Conclusion: The administration of HDMTX therapy was found to be safe without any life threatening adverse effect in a developing country like Bangladesh where there is lacking of lab support and adequate supportive management. Bangladesh J Child Health 2017; VOL 41 (1) :15-23